2010
DOI: 10.1002/anie.200907226
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Nanoparticulate Functional Materials (Angew. Chem. Int. Ed. 8/2010)

Abstract: Nanoscientists boldly go to the frontiers of the smallest solids in basic science and their technical application. In their Review on H. Goesmann and C. Feldmann point to the visionary potential of nanoparticulate functional materials. After a general introduction of the topic, the optical, electrical, magnetic, and catalytic properties of nanoparticles as well as their potential for upgrading materials are summarized. Moreover, fundamentally novel shapes and compositions of matter are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
277
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(285 citation statements)
references
References 0 publications
1
277
0
1
Order By: Relevance
“…SPECT imaging uses gamma emitting radioisotopes such as Nanostructures, which range in size from 1 to 100 nm, have a high surface area to volume ratio and strong, controllable binding capacity for specific molecules. This allows for varied surface modification and the multivalent binding of targets, which suggests new applications in molecular imaging and nanomedicine [38][39][40][41][42][43][44][45][46][47][48]. While active targeting is advantageous, the most important factor of nanostructure development for bioimaging is the enhanced permeability and retention (EPR) effect due to the leakage of neovasculature in tumor.…”
Section: Reviewmentioning
confidence: 99%
“…SPECT imaging uses gamma emitting radioisotopes such as Nanostructures, which range in size from 1 to 100 nm, have a high surface area to volume ratio and strong, controllable binding capacity for specific molecules. This allows for varied surface modification and the multivalent binding of targets, which suggests new applications in molecular imaging and nanomedicine [38][39][40][41][42][43][44][45][46][47][48]. While active targeting is advantageous, the most important factor of nanostructure development for bioimaging is the enhanced permeability and retention (EPR) effect due to the leakage of neovasculature in tumor.…”
Section: Reviewmentioning
confidence: 99%
“…In this field, the unique properties of nanoparticles enable reactions that were not possible or significantly low yielding when using conventional catalysts [141]. Plant synthesized Au nanoparticles have offered exciting possibilities in catalysis for pollution reduction.…”
Section: Environmentally Relevant Catalysismentioning
confidence: 99%
“…Work has demonstrated that TiO 2 nanoparticles are excellent catalysts for applications including photocatalysis, dye-sensitized solar cells and photovoltaic cells [143]. While bulk TiO 2 is relatively non-conducting and therefore ineffective in these processes, efficient electron transport is achieved through the large surface area of nanoparticles [141]. Mahmood et al [144] have shown the potential for use of plant synthesized TiO 2 nanoparticles, formed by phytoextraction using water hyacinth, as effective photocatalysts for the production of syngas.…”
Section: Environmentally Relevant Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, to meet the requirements for cellular delivery, iron oxide nanoparticles (IONPs) have to be subjected to chemical modification, such as strong affinity between the carriers and biomolecules, as well as a good biocompatibility, amongst others, for example to allow for targeting or to enhance circulation times. Surface modification of these NPs can improve the interaction between NPs and biomolecules 9,10 . Modified NPs as carriers for drugs and biomolecules have several advantages, such as the grafting of specific biomolecules onto NPs able to provide site specific delivery into cells 11 .…”
Section: Introductionmentioning
confidence: 99%